A Nanospherical Ordered Mesoporous Lewis Acid Polymer for the Direct Glycosylation of Unprotected and Unactivated Sugars in Water1. Issue 32 (23rd July 2014) - Zhang, Fang; Liang, Chao; Wu, Xiaotao; Li, Hexing
Abstract The design of robust solid catalysts which can selectively synthesize highly functionalized carbohydrate derivatives from unprotected and unactivated simple sugars in water is an outstanding challenge. Herein we describe the preparation of a novel nanospherical ordered mesoporous Lewis acid polymer (Sc(OTf)2‐NSMP) by functionalizing the mesoporous phenol‐formaldehyde polymer framework with scandium triflate groups. In the C‐glycosylation reaction between D‐glucose and dimedone with the Sc(OTf)2‐NSMP catalyst, the conversion was 99 % and the yield of xanthone‐C‐glucoside reached 92 % after 2 days, which exceeded the previous best results. It was shown that other xanthone glycosides can be obtained from various sugars with moderate to good yields. Furthermore, the catalyst can be easily recovered and reused at least seven times without loss of catalytic activity.